The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/08862605211021961
|View full text |Cite
|
Sign up to set email alerts
|

Troubling Trade-offs Between Women’s Work and Intimate Partner Violence: Evidence From 19 Developing Countries

Abstract: The empirical link between women’s employment status and their experience of different types of intimate partner violence (IPV) is not very apparent. Using Demographic and Health Surveys (DHS) data from 19 developing countries in South Asia, Sub-Saharan Africa, and the Middle East, we found that working women were significantly more likely to experience IPV than their stay-at-home counterparts. Given the great diversity in women’s employment with respect to economic returns and working conditions, we disaggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The absence of these opportunities can facilitate male control over women and a lack of recourse in response to male aggression, as evidenced by the observation that intimate partner violence and other forms of abuse in industrialized societies often involve attempts to isolate victims from their networks, such as those developed at work [6568]. Employment, and the networks developed therein, can be protective against intimate partner violence ([69], but see [70]). In support of this idea, gendered violence is virtually unknown among the Batek [33], whereas intimate partner violence is not uncommon among Tsimane [71].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of these opportunities can facilitate male control over women and a lack of recourse in response to male aggression, as evidenced by the observation that intimate partner violence and other forms of abuse in industrialized societies often involve attempts to isolate victims from their networks, such as those developed at work [6568]. Employment, and the networks developed therein, can be protective against intimate partner violence ([69], but see [70]). In support of this idea, gendered violence is virtually unknown among the Batek [33], whereas intimate partner violence is not uncommon among Tsimane [71].…”
Section: Discussionmentioning
confidence: 99%
“…These results coincide with those found in other studies whereby women’s economic power was positively related to their risk of suffering IPV ( Casique, 2003 ; Flake, 2005 ; Castro et al, 2008 ; Ludermir et al, 2008 ; Nguyen et al, 2008 ; Rahman et al, 2011 ). For example, a recent study found that across 19 countries in Sub-Saharan Africa, the Middle East, and South Asia, women who were working were significantly more likely to be subjected to IPV than those who were not ( Zafar et al, 2021 ). A possible explanation might be that women who are working could be seen to be violating a prescribed traditional gender norm where women’s traditional role may be perceived to be as a homemaker.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not consistent with studies reporting higher IPV levels if women work, particularly if they earn more than their husbands (Abramsky et al, 2019; Gage & Thomas, 2017). It may reflect the diversity in economic returns and working conditions associated with women’s employment (Zafar et al, 2021), producing differential effects across regions (Amegbor & Pascoe, 2021)—observed in the GWR model. More likely, it is because of the multicollinearity noted earlier (the correlation between FWPR and SCSTP is high).…”
Section: Discussionmentioning
confidence: 99%